Disposable (bio)chemical integrated optical waveguide sensors implemented on roll-to-roll produced platforms. Issue 56 (23rd May 2016) - Aikio, Sanna; Zeilinger, Martin; Hiltunen, Jussi; Hakalahti, Leena; Hiitola-Keinänen, Johanna; Hiltunen, Marianne; Kontturi, Ville; Siitonen, Samuli; Puustinen, Jarkko; Lieberzeit, Peter; Karioja, Pentti
Abstract : Demonstration of disposable multi-analyte polymeric integrated Young interferometers for analyte specific chemical- and biochemical sensing using biological and biomimetic recognition. Abstract : To enable wide spread dissemination of sensors in cost-critical applications and resource poor settings, methods to implement sensor chips using low-cost materials and mass-manufacturing methods are developed. In this paper we demonstrate that disposable polymeric integrated Young interferometer (YI) sensor chips, implemented on roll-to-roll mass-manufactured waveguides, are applicable for analyte specific sensing of small molecules and for multi-analyte detection of biomolecules. For the chemical sensing of small molecules, a sensor chip was functionalized with a molecularly imprinted polymer (MIP). We demonstrate that the MIP receptor layer is compatible with a polymer-based evanescent wave sensor for direct refractive index sensing. For multi-analyte detection of biomolecules, antibody-based receptor layers were patterned by inkjet printing onto the sensor surface demonstrating the applicability of the method with integrated YI chips. Demonstration of the analyte specific chemical- and biosensing with disposable polymeric YI sensor chips opens new possibilities to implement low-cost (bio)chemical sensors.